Produção de proteases por Aspergillus em fermentação semi-sólida utilizando torta de canola - Freitas, Adriana Crispim de (2009)
The proteases belong to the class of enzymes with the capacity to hydrolyze peptidic connections into protein and protein fragments, modifying the substrate by great selectivity and specification. The semi-solid fermentation is a fermentation process in which the growth of microorganisms and the formation of the products occur on the surface of the solid substrate next to the absence of free water, usually using natural raw materials as a source of carbon and energy. On this study, it was done the semi solid cultivation of filament fungi, in order to produce proteases using as a substrate a cake of canola. It was evaluated, in a first study, the potential of different strains of Aspergillus for the production of proteases. The strains studied were Aspergillus niger (CNPAT 001, IOC 207, IOC 4222, IOC 4220 and IOC 3883) and Aspergillus oryzae IV. The best strain obtained for the production of protease was a strain of Aspergillus oryzae IV. Later on, it was studied the influence of the different quantities of water and coke canola added; the best production was obtained in proportion with 40 mL of water to 100 g of cake. After determination to medium of moisture, was evaluated the temperature of incubation, the best results were obtained in media incubated at 20° C. Further, studies were done to determine the best concentration of inoculum, the concentrations tested were 1 × 104, 1 × 105, 1 × 106 and 1 × 107 spores per gram of medium, being 1 × 107 to better concentration analyzed. The influence of supplementation of fermentation medium with sources of phosphorus, carbon and nitrogen was evalueted. Supplementation of the cake of canola, with 1% (w/w) monobasic sodium phosphate did not influence positively the production of proteases. Supplementation of medium with different sources of nitrogen were studied in the proportion of 1.0% (w/w) in the weight of the substrate, being the yeast extract of the best source evaluated, showing increased production of proteases. Then, it was tested the incubation period of the medium without supplementation of nutrients, between 0 and 240 hours of fermentation with samples being removed every 24 h of fermentation process. The highest production occurred at 96 h with production of 336 U.g-1 protease. After this stage, was evaluated the supplementation of medium with different carbon sources at different concentrations, 1.0, 2.0, 3.0, 4.0, 5.0, 7.5, 10.0, 12, 5 15.0 % (w/w) in the weight of the substrate; the increased production of proteases occurred in the medium with the addition of glucose at a concentration of 7.5 % obtaining 452 Ug-1. In the last stage, was performed the characterization of the medium during the fermentation process by of a chemical and physicochemical analytical determinations. The increased production of proteases obtained was 452 U.g-1 in 96 hours of fermentation process, in media supplemented with 7.5 % glucose, at the fermentation conditions: temperature of incubation of the medium at 20° C, damp cake with 40 mL water per 100 g of substrate and concentration of inoculum of 1 × 107 spores.g-1.